Iron-Mediated Bromocyclization of Olefinic Amides for the Synthesis of Bromobenzoxazines - Zhao, Tong-Tong; Bian, Qiang; Zhao, Yu-Wei; Xu, Lin-Lin; Xu, Da-Zhen; Zhao, Wei-Guang (Synthesis, 2024)
An iron-mediated bromination/cyclization for the synthesis of bromobenzoxazines from olefinic amides has been successfully developed. In this protocol, the simple iron salt FeBr3 was employed as a bromination reagent, giving the bromobenzoxazine products in moderate to excellent yields. This methodology features good functional group tolerance, gram-scale synthesis, and green reaction conditions by the use of air as the terminal oxidant. Preliminary mechanistic studies suggest that a free radical pathway is involved.
Keywords: benzoxazines; bromination; iron salts; aerobic oxidation; molecular oxygen